PERSEPSI GURU DAN SISWA TENTANG EFEKTIVITAS MANAJEMEN KURIKULUM DAN PENGARUHNYA TERHADAP KREATIVITAS SISWA SEKOLAH MENENGAH ATAS - Sesanti, Alma’idah Hayuning; Burhanuddin, Burhanuddin; Ulfatin, Nurul (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
The study aims to know teachers and students perception about curriculum management effectiveness and the effect to State High School students creativity. The study used a quantitative approach with predictive correlational design. The population in this research are 569 teachers and 3.117 11th grade students from 10 Malang’s State High Schools. The samples of teacher are taken by using quota sampling and random sampling as the techniques, then the samples of student are taken by using purposive sampling. The samples in this research are 234 teachers and 312 students. Data analysis techniques those have been used are descriptive statistical analysis, normality test, linearity test, simple regression analysis, and oneway anova analysis. The results of this research show that in the entire Malang’s State High School (1) curriculum management is quite effective; (2) students creativity level is high enough; (3) there is a significant influence of the curriculum management effectiveness to student creativity level; (4) there is no difference in teacher perception of curriculum management effectiveness level based on organizational factors, (5) there is no difference in student perception of self-creativity level based on individual factors, and (6) there is no difference in student perception of self-creativity level based on social factors.